Women, chronic illness, and rural Australia: Exploring the intersections between space, identity, and the body - Pini, B.; Soldatic, Karen (2012)
This chapter brings a rural dimension to the literature on women and chronic illness by drawing on the story of an Australian rural woman who has chronic fatigue syndrome, or myalgic encephalomyelitis (ME). Integral to this literature is Moss and Dyck’s (2002) book-length exploration of the lives of forty-nine women who had been diagnosed with either ME or rheumatoid arthritis (RA), along with their other writings on the topic (e.g., Dyck, 1995a, 1995b; Moss 1997; Moss & Dyck, 1996, 1999a, 1999b, 2001).